A review of solid oxide fuel cell component fabrication methods toward lowering temperature - Zakaria Z.; Awang Mat Z.; Abu Hassan S.H.; Boon Kar Y. (John Wiley and Sons Ltd, 2023)
Anodes; Cathodes; Electrodes; Electrolytes; Energy conversion; Fabrication; Fuel cell power plants; Gas fuel purification; Solid oxide fuel cells (SOFC); Energy productions; Fabrication method; Operating temperature; Portable applications; Power plant stations; Small scale power generation; Solid oxide fuel cells (SOFCs); Stationary applications; Solid electrolytes